Reducing risk in the emerging markets: Does enhancing corporate governance work? - Naz Sayari; Bill Marcum (BRQ Business Research Quarterly, 2018)
This study examines emerging market firms that adopt corporate governance standards similar to those in the US. The investigation highlights the impact governance standards may have on corporate risk taking, as measured by stock return volatility, under varying political and socioeconomic regimes. In a cross-sectional time-series setting, the analysis reveals that enhanced governance standards are associated with risk reductions among US domiciled firms, cross-listed American Depository Receipt companies (ADRs) and non-cross listed emerging market (EM) firms. The effect of these governance standards on risk taking, however, does not deviate considerably between cross-listed ADRs that are exposed to Securities and Exchange Commission (SEC) mandated regulations and non-cross-listed EM firms that are not subject to the same regulatory constraints. Also, in some respects, Chinese firms seem to exhibit corporate behavior that is contrary to that of the rest of the world."
Keywords: 650; Corporate governance; Risk; Emerging markets; American Depository Receipts (ADRs); Securities and Exchange Commission (SEC) regulations